THE ROLE OF MYCOPLASMA PNEUMONIA AS ETIOLOGICAL AGENT IN DISEASE OF RESPIRATION TRACTS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
In this paper is given the data of the last 10 years about etiological role of Mycoplasma pneumonia and frequency of occurrence in upper respiratory tract dieses clinics, immunity and also up to – date methods of diagnostics and analysis of literature about measures by treatment of M.pneumonia makes up 25% atypical pneumonia 10-16% from total number of acute respiratory dieses.